Arsenic and total dissolved solids removal using antibacterial/antifouling nanofiltration membranes modified by functionalized graphene oxide and copper ferrodioxide - Gholami, Foad (Water environment research : a research publication of the Water Environment Federation, 2023)
© 2023 Water Environment Federation.